Reimagining curricula: effects of cultural (in)sensitivity of curricula on racially minoritised students' engagement - Thomas, Dave S. P.; Quinlan, Kathleen M. (Studies in higher education (Dorchester-on-Thames), 2023)
Imperatives to eliminate racial inequalities in higher education (HE) have led to calls for diversification of curricula. Qualitative evidence is growing about racially minoritised students' perceptions of their curricula and its impact on them. Yet there are no specific instruments to facilitate evaluation of curricular diversification and its impact on students. We examined the relationship between students' perceptions of the cultural sensitivity of their curriculum and their engagement, as measured by students' interactions with their teachers and their interest in their programme of study. To do so, we conceptualised and developed a new set of four Culturally Sensitive Curriculum Scales, making a significant, original conceptual and methodological contribution. A racially diverse sample of second through postgraduate students primarily in arts, humanities and social sciences (N = 262; 189 F) rated the cultural sensitivity of the curriculum of their programme, their interactions with teachers, and their interest. Racially minoritised students (n = 157) perceived their curriculum as less culturally sensitive on all four dimensions, reported fewer academic interactions with teachers, and had lower levels of interest than White students (n = 100). Each of the four Culturally Sensitive Curriculum Scales was significantly related to academic interactions with teachers and to interest. Regression analyses showed that all dimensions of cultural sensitivity mediated effects of ethnicity on interactions with teachers. Two dimensions of cultural sensitivity (Diversity Represented and Challenge Power) mediated effects of ethnicity on interest. Therefore, ensuring curricula are diverse and critical may support racially minoritised students' engagement, potentially contributing to reducing achievement gaps. Further implications are discussed.